Pengembangan Media Interaktif Berbasis Mind Mapping dengan Aplikasi Macromedia Director MX 2004 Pada Mata Pelajaran IPS Untuk kelas IX SMP - Novrianti Novrianti (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
This research is a procedural development with research subjects 4 respondents, consisting of two people validator media experts and two experts: two lecturers material UNP and two Masters SMP N 1 Batusanggkar. The instrument includes the content of the material aspects and aspects of the media. Data was analyzed by qualitative descriptive to determine the quality of interactive multimedia in teaching IPS.Hasil analysis pointed that the interactive multimedia teaching material, entitled Development-based Interactive Media Mind Mapping with director Macromedia MX 2004 applications for learning social studies to junior class IX are packaged in a CD Learning this into Category Very Baik.Berdasarkan Results deskripstif test data experts point out that this interactive multimedia teaching materials fit for use as a source of learning and alternative media in solving problems of social studies in junior high.